2014
DOI: 10.1186/1465-9921-15-8
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and endurance training effects on quantity and quality of pulmonary vascular bed in healthy men

Abstract: It has recently been demonstrated that in healthy individuals, peak oxygen consumption is associated with a greater pulmonary capillary blood volume and a more distensible pulmonary circulation. Our cross-sectional study suggests that, in healthy men aged 20 to 60 years (n = 63), endurance sport practice (vigorous-intensity domain of the International Physical Activity Questionnaire) is associated with better quantity (pulmonary capillary blood volume) and quality (slope of increase in lung diffusion for carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…Our findings are confirmatory that healthy aging is associated with a progressive decline in resting DL CO (1,6,9,11,15,33,34). For example, Guénard and Marthan (15) demonstrated that both DL CO and DL CO relative to minute ventilation (DL CO /V E) are negatively correlated with age according to the equations DL CO ϭ 126 -0.90 ϫ age and DL CO /V E ϭ 13.5 -0.85 ϫ age, respectively.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Our findings are confirmatory that healthy aging is associated with a progressive decline in resting DL CO (1,6,9,11,15,33,34). For example, Guénard and Marthan (15) demonstrated that both DL CO and DL CO relative to minute ventilation (DL CO /V E) are negatively correlated with age according to the equations DL CO ϭ 126 -0.90 ϫ age and DL CO /V E ϭ 13.5 -0.85 ϫ age, respectively.…”
Section: Discussionsupporting
confidence: 86%
“…: Old Highly Fit (HF); □: Old. age (1,6,11,12,15,33,34). Interestingly, however, we also found that DL CO , Dm CO , and Vc were greater during maximal exercise in highly fit older individuals compared with their less fit age-matched counterparts (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations